2008
DOI: 10.1165/rcmb.2007-0177oc
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Dysregulated Na+ Absorption in Airway Epithelial Cells with Mucosal Nystatin Treatment

Abstract: In cystic fibrosis (CF), the absence of functional CFTR leads to dysregulated Na 1 absorption across airway epithelia. We established an in vitro model of dysregulated Na 1 absorption by treating polarized normal human bronchial epithelial cells (HBEs) with nystatin (Nys), a polyene antibiotic that enables monovalent cations to permeate biological membranes. Acute mucosal Nys produced a rapid increase in short circuit current (I sc ) that reflected increased transepithelial Na 1 absorption and required Na 1 /K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…This hypothesis is consistent with recent data that suggest that bypassing the normal regulation of ENaC at low ASL volumes with an unregulated "exogenous channel" (e.g. nystatin) can produce a phenotype of ASL depletion and mucus adhesion to airway surfaces (64). In the mouse experiments described here and in human bronchial epithelial cells treated with mucosal nystatin (64), the persistence of the capacity to secrete Cl Ϫ is not sufficient to protect the hydration status of the airway surface.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This hypothesis is consistent with recent data that suggest that bypassing the normal regulation of ENaC at low ASL volumes with an unregulated "exogenous channel" (e.g. nystatin) can produce a phenotype of ASL depletion and mucus adhesion to airway surfaces (64). In the mouse experiments described here and in human bronchial epithelial cells treated with mucosal nystatin (64), the persistence of the capacity to secrete Cl Ϫ is not sufficient to protect the hydration status of the airway surface.…”
Section: Discussionsupporting
confidence: 92%
“…nystatin) can produce a phenotype of ASL depletion and mucus adhesion to airway surfaces (64). In the mouse experiments described here and in human bronchial epithelial cells treated with mucosal nystatin (64), the persistence of the capacity to secrete Cl Ϫ is not sufficient to protect the hydration status of the airway surface. This result probably reflects the inability of airway epithelia to generate driving forces sufficient to secrete Cl Ϫ in the absence of ENaC inhibition (65).…”
Section: Discussionmentioning
confidence: 88%
“…This is consistent with a mitochondrial accumulation of Na + and water molecules as a result of an increase in the Na + influx through the nystatin pores with a simultaneous osmotically driven H 2 O influx. 34 Similar results were obtained with monensin. Small variations were observed with rotenone, artesunate and artemisinin.…”
Section: Mitochondrial Polarity Monitoring Using the Mmpsupporting
confidence: 71%
“…Nystatin, a polyene antibiotic that enables monovalent cations to permeate biological membranes and raise Na + /K + ATPase activity, did not produce significantly different I SC responses when applied to vehicle- or VX-770-treated HBE cultures (Fig. 6C, Table S10), suggesting intact Na + /K + ATPase activity (37). Measurements of intracellular concentrations of VX-809 and VX-770 by mass spectrometry confirmed the presence of these compounds in treated HBE cultures and indicated that cellular VX-809 concentrations were not affected by the presence of VX-770 (Fig.…”
Section: Resultsmentioning
confidence: 99%